Small Molecule Antagonists of the Wnt/Beta-Catenin Signaling Pathway Target Breast Tumor-Initiating Cells in a Her2/Neu Mouse Model of Breast Cancer - Hallett, Robin M.; Kondratyev, Maria K.; Giacomelli, Andrew O.; Nixon, Allison M. L.; Girgis-Gabardo, Adele; Ilieva, Dora; Hassell, John A. (PLOS ONE, 2012)
Background Recent evidence suggests that human breast cancer is sustained by a minor subpopulation of breast tumor-initiating cells (BTIC), which confer resistance to anticancer therapies and consequently must be eradicated to achieve durable breast cancer cure. Methods/Findings To identify signaling pathways that might be targeted to eliminate BTIC, while sparing their normal stem and progenitor cell counterparts, we performed global gene expression profiling of BTIC- and mammary epithelial stem/progenitor cell- enriched cultures derived from mouse mammary tumors and mammary glands, respectively. Such analyses suggested a role for the Wnt/Beta-catenin signaling pathway in maintaining the viability and or sustaining the self-renewal of BTICs in vitro. To determine whether the Wnt/Beta-catenin pathway played a role in BTIC processes we employed a chemical genomics approach. We found that pharmacological inhibitors of Wnt/β-catenin signaling inhibited sphere- and colony-formation by primary breast tumor cells and primary mammary epithelial cells, as well as by tumorsphere- and mammosphere-derived cells. Serial assays of self-renewal in vitro revealed that the Wnt/Beta-catenin signaling inhibitor PKF118–310 irreversibly affected BTIC, whereas it functioned reversibly to suspend the self-renewal of mammary epithelial stem/progenitor cells. Incubation of primary tumor cells in vitro with PKF118–310 eliminated their capacity to subsequently seed tumor growth after transplant into syngeneic mice. Administration of PKF118–310 to tumor-bearing mice halted tumor growth in vivo. Moreover, viable tumor cells harvested from PKF118–310 treated mice were unable to seed the growth of secondary tumors after transplant. Conclusions These studies demonstrate that inhibitors of Wnt/β-catenin signaling eradicated BTIC in vitro and in vivo and provide a compelling rationale for developing such antagonists for breast cancer therapy.